Synthesis of heterocycle based carboxymethyl cellulose conjugates as novel anticancer agents targeting HCT116, MCF7, PC3 and A549 cells - Reham A. Mohamed-Ezzat; Zeinab A. Elshahid; Shaimaa A. Gouhar; Sawsan Dacrory (Scientific Reports)
Abstract Toward developing anticancer agents, heterocycle-based carboxymethyl cellulose conjugates have been synthesized. 2-Cyano-N′-(aryl/heteroarylethylidene)acetohydrazides and ethyl 2-cyano-3-(heteryl)acrylates were utilized as precursors for the synthesis of pyridine-based compounds. The chemical structures of the synthesized derivatives were characterized using various spectroscopic techniques, including 1H-, 13C-NMR, Fourier transform infrared spectroscopy (FTIR), as well as scanning electron microscopy (SEM).The anticancer effects of compounds on HCT-116, MCF-7, PC3 and A549 cancer cell lines were investigated and their cytotoxicity against RPE-1 normal cells was estimated to determine their safety. Compounds 4b and 7c exhibit high selectivity toward cancer cells while maintaining a strong safety margin for normal cells. The results demonstrated that the novel heterocycle-based carboxymethyl cellulose conjugates are promising and can be further evaluated as a potential therapeutic agent.